ASEAN's ROLE IN CYBERSECURITY MAINTENANCE AND SECURITY STRATEGY THROUGH AN INTERNATIONAL SECURITY APPROACH - Khotimah Estiyovionita; Afandi Sitamala (Lampung Journal of International Law, 2022)
The development of information and communication technology makes it easier for humans to access everything without being limited by time, space, and distance so that they are connected in one space. Given cyberspace's borderless and anonymous characteristics, it encourages the emergence of criminal activities, namely cybercrime. Therefore, as a measure to prevent future damage, it requires not only regulatory laws and regulations but also international cooperation between countries is needed. These cooperation efforts can be implemented through the forum of regional organizations, namely ASEAN. Until now, many efforts have been made to encourage the improvement of cybersecurity through its various programs. Therefore, it is hoped that this increase in cooperation will further strengthen cybersecurity in the region to maintain security stability.